(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The current issues of increasing the efficiency of sowing grain crops in the context of the implementation of resource-saving agricultural technologies mini-till and no-till are considered. A review of modern sowing machines, design features of seeders from different manufacturers, as well as technical and technological solutions aimed at improving the quality of sowing is conducted. Design solutions used in sowing machines from leading domestic and foreign manufacturers are analyzed, in particular the designs of openers, wrappers, clamping mechanisms and copying systems. Effective implementations of technical solutions that ensure high-quality sowing in fields with a large amount of crop residues and with a changed soil structure are presented. The research results provide an opportunity to form an idea of promising areas for improving seeding machines and increasing the efficiency of their use in sustainable farming systems.